Undergraduate research in the Dartmouth Economics Department. Issue 4 (2nd October 2017) - Feyrer, James
ABSTRACT: One of the key components to the undergraduate research enterprise at Dartmouth is the recognition that learning to do research requires both directed instruction and learning by doing. The economics faculty have tailored a fruitful undergraduate research program based on this philosophy, and this article describes these efforts while also offering advice to other programs as they strive to involve undergraduates in research.